Специфические функции заработной платы как экономической категории в условиях рыночных отношений - Губаренко, И. И.; Смоловик, Раиса Федоровна (НТУ "ХПИ", 2013)
This article discusses the functions of salary, deficiencies in the process of building the pay system, offers activities to its improvement, taking in to account its interrelationship with social challenges.
Keywords: доход трудовой; рынок труда; премия; сила рабочая; производительность труда; распределение дохода